Banking Umbilical Cord Blood (UCB) Stem Cells: Awareness, Attitude and Expectations of Potential Donors from One of the Largest Potential Repository (India) - Pandey, Deeksha (PLoS One, 2016)
BACKGROUND: The concept of Umbilical Cord blood (UCB) stem cells is emerging as a non-invasive, efficacious alternative source of hematopoietic stem cells to treat a variety of blood and bone marrow diseases, blood cancers, metabolic disorders and immune deficiencies. Aim of the present study was to determine the level of awareness about banking UCB among pregnant women in India. We also assessed patient perception for banking of UCB and explored the patient expectations of banking UCB in future. This is the first study to assess current attitudes, in a sample population of potential donors from one of the largest potential UCB repository (India). Obtaining this information may help optimize recruitment efforts and improve patient education. MATERIAL AND METHOD: Present explorative questionnaire based survey included 254 pregnant women in the final analysis. RESULTS: We established only 26.5% pregnant women in our study population knew what exactly is meant by UCB. A large proportion (55.1%) was undecided on whether they want to bank UCB or not. Women were more aware of the more advertised private cord blood banking compared to public banking. More than half of the pregnant women expected their obstetrician to inform them regarding UCB. One-third of the women in our population had undue expectations from banking of the UCB. CONCLUSION: Obstetricians should play a more active role in explaining the patients regarding pros and cons of UCB banking.